The Cost of Reform : How the 1906 Meat Inspection Act Reshaped America’s Position in World Meat Trade - Cerhová, Irena; Johnson, Zdenka, 1983-; Chalupecký, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis examines how the Meat Inspection Acts shaped U.S. meat exports and the structure of the meat-packing industry. The central hypothesis is that while large packing firms already held a dominant position, the 1891 Act reinforced their export advantage, whereas the 1906 legislation deepened domestic consolidation and contributed to a gradual loss of U.S. export dominance. The theoretical part introduces the historical and institutional background of federal meat inspection and outlines the relevant economic theories of information asymmetry and regulation, drawing on the work of Akerlof, Stigler, and Peltzman. The analytical part combines descriptive statistics, regression analysis, and comparative methods to assess changes in export prices and volumes, industry concentration, and the role of Argentina in reshaping international competition. The findings indicate that export prices declined in the 1880s following European import restrictions linked to disease concerns but recovered after the introduction of federal inspection in 1891, consistent with Akerlof’s mechanism of information asymmetry. The initial expansion of exports was supported by technological change that enabled the rapid growth of large packing firms in both domestic and foreign markets, while the total number of establishments did not decline. After 1906, consolidation increased among firms operating in interstate commerce, whereas smaller producers continued to serve local markets. Internationally, Argentina’s specialization in high-quality beef altered global competition, prompting U.S. firms, facing declining export performance, to invest directly in Argentine production and trade.
Vedoucí práce: Zdenka Johnson
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: moderní hospodářské dějiny [obor dipl. práce]; diplomové práce; master's theses